Encyclopedic dictionary of hydrogeology - Poehls, D. J. (Academic Press/Elsevier, 2009)
The scientific disciplines of hydrology and hydrogeology are expanding as the Earth's water is being recognized by governments and individuals as a shrinking resource-no entity can afford to take water for granted. At the present time, there is no single reference source for definitions. The Encyclopedic Dictionary of Hydrogeology is a practical, comprehensive reference guide with complete definitions of terms in hydrogeology and other fields closely related to water practices. This concise reference not only defines terms and concepts, but also provides a clear explanation of key el.
Keywords: Hydrogeology -- Dictionaries.; elektronické knihy; electronic books